Combining Microwave and Optical Sensor to Improve Post Cyclone Affected Area Mapping - Sarker, MH; Akter, M; Ali, S; Haque, SAM Arif Ul; Rahman, M (Journal of Environmental Science and Natural Resources, 2021)
Storm surge was adversely affected the life of people and property of coastal region of Bangladesh due to cyclone Roanu on 22 May 2016. It is important to delineate this surge extent and pattern which helps in the vulnerability assessment for relief and rehabilitation purposes. Optical sensor is not enough for outlining the affected areas. Because during cyclone, bad weather (cloud) usually prevails over the swamped area. Microwave remote sensing, can solve the problem because the radar pulse can penetrate cloud cover and it has ability to sharply distinguish between land and water. Combination of microwave and optical sensor found very useful to mark out storm surge inundated area. A change detection approach was implemented through the analysis of pre and post cyclone period. In this approach Landsat8-OLI image have been used for before cyclone and ALOS-PALSAR image have been used in after cyclonic period. Combining the PALSAR and OLI imagery using fusion method allows for the accurate depiction of such kind of violence surge extend. The study reveals that about 497698 (ha) areas have been affected due to storm surge during cyclone Roanu. Environ. Sci. & Natural Resources, 12(1&2): 1-9, 2019